ANALISIS USAHA PETERNAKAN BROILER POLA KEMITRAAN DAN PETERNAKAN MANDIRI DIKABUPATEN DELI SERDANG (STUDI KASUS PADA PT SATWA UTAMA RAYA) - Glorya Febrina Situmorang (Universitas Sumatera Utara, 2013)
ABSTRACT The aims of the research were to compare income and R/C ratio value Analysis of Broiler breeding business partnership and non_partnership On Deli Serdang District (case study on PT. SUR). The research was conducted at Pancur Batu, Namorambe and Tanjung Anom Subdistrict, Deli Serdang District, Starting from Juni until August 2012. Research method used survey using purposive sampling with nine sample for each partnership and non-partnership. The data were analized using t-test. The results income analysis showed that profit non-partnership is Rp 1.624,26/head, and PT Satwa Utama Raya is Rp 1. 890,05/head. The analysis ratio show that R/C ratio non-partnership is 1,07 and partnership is 1,10. The analysis ratio show that R/C ratio non-partnership was 1,07 and partnership is 1,10. t-tes result show that beetwen non-partnership and PT Satwa Utama Raya It not show significant differences (P>0,05). It was conclude that broiler farm business at PT satwa utama raya partnership and non-partnership not show significant differences. Keywords: Partnership, Non-Partnership, Broiler, R/C ratio, Income.